2005
DOI: 10.1002/adma.200400984
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanoparticle Mobility on Toughness of Polymer Nanocomposites

Abstract: In the past decade, attention has been focused on using polymer nanocomposites to overcome the trade-offs encountered in traditional composite systems.[1±12] Notwithstanding an increase in stiffness, most reported nanocomposites exhibit lower toughness than the matrix polymers, although Cohen and co-workers have found that some particulate-filled polymer composites show an increase in toughness compared to the neat polymer.[13±15] They attributed the effect to the combined mechanisms of crack deflection and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
187
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(198 citation statements)
references
References 15 publications
10
187
1
Order By: Relevance
“…Specifically, we note the organization of the polymer matrix into fiber-like conformations and superstructures oriented parallel to the stretching direction. In rubbery matrices, the realignment of the clay particles themselves along the stretching direction effectively blocks crack propagation and deflection [41,42].…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, we note the organization of the polymer matrix into fiber-like conformations and superstructures oriented parallel to the stretching direction. In rubbery matrices, the realignment of the clay particles themselves along the stretching direction effectively blocks crack propagation and deflection [41,42].…”
Section: Methodsmentioning
confidence: 99%
“…When the content of ZnO increases further, the nanocomposites display not only a reduced peak intensity but also disappearance of some peaks and occurrence of a new reflection peak. It is well known that the incorporation of nanoparticles would result in the formation of β phase [6,19] . In our study, it was found that when the content of ZnO nanorods reach as high as 20 wt%, the new developed β phase can be easily seen, which is consistent with the study reported previously [2,7,20] .…”
Section: Crystal Structure Transformation Of P(vdf-hfp) and Its Nanocmentioning
confidence: 99%
“…Through the β phase is not a stable phase compared with the α phase, it still raises a lot of research interest, since it has an impressive effect on the piezoelectric and pyroelectric properties [5] . To date, numerous fillers, such as nanoclay [6,7] , carbon nanotubes [8] , and graphene sheets [9,10] have been used as an effective method for the forming of β phase PVDF. However, there are only several literatures about P(VDF-HFP) based composites.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamical arguments are based on the observation that a PNC, where NPs are more mobile than the polymer chains, achieves a better resistance against deformation via improved release of local tension. 17,18,33,34 The structural arguments relate the NPs ability to create temporary bonds between the chains, thus creating a NP-polymer network, to the mechanical properties of the PNC. 19,22,24,26,35,36 In a recent publication 28 we demonstrated that the mechanical properties of PNC loaded with small, spherical NPs are related to structural features, such as the filler loading, the surface area of the polymerfiller interface, and the polymer-filler network structure.…”
Section: Introductionmentioning
confidence: 99%